Review of the scientific magazine "Agroindustria, Sociedad y Ambiente" (issn 0798-0361) of the Centroccidental University Lisandro Alvarado (Revista Electrónica REDINE, 2021)
The journal Boletín Médico de Postgrado (ISSN 0798-0361) was created in 1985 and the editorial committee was chaired by Dr. Carlos Rivero. This journal is attached to the Postgraduate Coordination of the Dean of Health Sciences of the Universidad Centroccidental Lisandro Alvarado (UCLA). .It is a refereed and indexed journal, circulating every six months, created with the purpose of disseminating the results of the research carried out in the Dean of Health Sciences of the Universidad Centroccidental Lisandro Alvarado as well as international research in the field of human health.
Keywords: international research; UCLA; human health